2001
DOI: 10.1176/appi.ajp.158.3.492
|View full text |Cite
|
Sign up to set email alerts
|

Is Substance Abuse in Schizophrenia Related to Impulsivity, Sensation Seeking, or Anhedonia?

Abstract: As in the general population, high levels of impulsivity and sensation seeking are associated with substance abuse in patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
52
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(64 citation statements)
references
References 11 publications
7
52
1
4
Order By: Relevance
“…These data are consistent with other studies assessing impulsivity and sensation seeking in chronic schizophrenia patients with substance abuse disorders, including alcohol, cannabis, opiate, and cocaine use [23][24][25][26][27]. Zhonitsky et al suggested that: (i) substance abuse/dependence patients with and without schizophrenia are characterized by abnormally high sensation seeking; and (ii) non-abusing schizophrenia patients are characterized by abnormally low sensation seeking [28].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These data are consistent with other studies assessing impulsivity and sensation seeking in chronic schizophrenia patients with substance abuse disorders, including alcohol, cannabis, opiate, and cocaine use [23][24][25][26][27]. Zhonitsky et al suggested that: (i) substance abuse/dependence patients with and without schizophrenia are characterized by abnormally high sensation seeking; and (ii) non-abusing schizophrenia patients are characterized by abnormally low sensation seeking [28].…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the Zhonitsky study did not find significant differences in impulsivity between substance abuse/dependence patients with and without schizophrenia in discordance with sensation-seeking behavior. This is in discordance with our findings as well as the other studies above [23][24][25][26][27]. In line with several previous studies [23][24][25]28] and contrary to the belief that sensation seeking is a way of counteracting anhedonia in certain schizophrenia patients [29,30], we did not find a link between physical anhedonia scores and cannabis abuse in our population.…”
Section: Discussioncontrasting
confidence: 71%
“…In the other studies the mean age was higher [38,39] , except for the opiate addicts in the sample of Schmidt et al [16] in which a bimodal age distribution appeared, refl ecting the type of substance abused (opiates or alcohol), and the schizophrenic substance abusers in the study of Dervaux et al [46] . In all these studies the evaluation of anhedonia was performed during the early days of abstinence [16,39,46] ; only Marra et al [38] repeatedly assessed anhedonia at baseline and 2 and 6 months after withdrawal.…”
Section: Discussionmentioning
confidence: 85%
“…Since INA phase magazine entry results in a mild form of punishment in terms of a temporal delay in the onset of the CS-UCS sequence, NVHL effects on increasing the proportions of INA phase approaches, while reducing proportions of CS phase approaches, may model aspects of clinical constructs of impulsivity. Numerous studies have linked behavioral trait markers of impulsivity with SUDS in primary SUD patient populations (Bickel et al 1999;McGrue et al 2001;Petry 2001), psychiatric populations with SUD comorbidity (Anthony and Helzer 1991;Dervaux et al 2001;Moeller et al 2001) and periadolescent age groups with developmental-age vulnerability to addictions (Chambers et al 2003;Ernst etal. 2003).…”
Section: Discussionmentioning
confidence: 99%